Teaching Islamic Values Based On Multiple Intelligences In Early Childhood - M.Arzani; Hamidi; Muhajirin Ramzi (KASTA : Jurnal Ilmu Sosial, Agama, Budaya dan Terapan, 2025)
This study aims to analyse and describe the implementation of Multiple Intelligences (MI)-based learning in instilling Islamic values in early childhood in Lombok. The research uses a qualitative approach with a multi-site case study design conducted in three Islamic early childhood education institutions, namely Al-Iqro' Kindergarten in Mataram City, KB Riyadlusshibyan Early Childhood Education in West Lombok, and Insan Kaamil Teniga Kindergarten North Lombok. The research subjects included PAUD principals, teachers, children, and parents. Data were collected through in-depth interviews, non-participant observation, and documentation. Data analysis was conducted through the stages of data condensation, data presentation, and conclusion drawing. The results of the study indicate that the implementation of MI-based learning is able to accommodate the diversity of children's intelligence potentials, such as linguistic, kinesthetic, musical, interpersonal, intrapersonal, naturalistic, spiritual, and communal (Jama'ah) intelligence, which is a new finding of this study. The MI approach has been proven effective in helping internalise Islamic values in a contextual, enjoyable manner that is appropriate for the natural development of early childhood. This research contributes theoretically by strengthening the paradigm of Islamic education based on Fitrah and Ta'dib, as well as practically by providing a learning model called the Islamic Multiple Intelligences-Based Learning Environment for Islamic early childhood education